Effective Advertising and its Influence on Consumer Buying Behavior - Khan, Ghulam Shabbir; ., Burhan Ali Shah; ., Ahmed Imran Hunjra (Information Management and Business Review, 2012)
Advertising is a way of communication to convince an audience for taking purchase decision about a product or service and delivering information to viewers. This paper examines the relationship between environmental response and emotional response which are independent variables with dependent variable i.e. consumer buying behavior. This research investigates the relationship between the variables involved, by taking the 200 responses in twins’ cities of Pakistan. Findings of this study show the moderate relationship between independent variables and dependent variable. It shows that consumer purchase those brands from which they are emotionally attached. This study reports new results in the field of buying behavior of consumers’ response.